Diversity of saprobic fungi on magnolia garrettii: Do collecting sites and seasons affect the fungal community? - R. Kodsueb (2020)
© 2019 Penerbit Universiti Kebangsaan Malaysia. All rights reserved. The diversity of saprobic fungi found on woody litter of Magnola garrettii collected from Phu Hin Rongkla National Park in Phitsanulok Province, Thailand during the wet and dry seasons, from July 2008 to April 2009, was studied, and the fungal diversity and community was compared with a previous study in Doi Suthep-Pui National Park in Chiang Mai Province. Based on morphological characteristics, 141 taxa were obtained and classified as 40 Ascomycetes, 5 Basidiomycetes, 42 lichens, one unidentified taxon and 53 anamorphic fungi. The number of taxa recovered indicated that Dry season samples supported a more diverse fungal community than samples collected in the wet season, for both collecting sites, although the common genera of fungi obtained during each season were similar. Distinct fungal communities of saprobic fungi collected from each site suggest that site characteristics affect the community composition. Samples from Phu Hin Rongkla National Park provided higher numbers of fungi (especially lichens) than were collected in the previous Doi Suthep-Pui National Park study with few species overlapping in the two sites.